2020
DOI: 10.3390/s20020559
|View full text |Cite
|
Sign up to set email alerts
|

Improving Depth Resolution of Ultrasonic Phased Array Imaging to Inspect Aerospace Composite Structures

Abstract: In this paper, we present challenges and achievements in development and use of a compact ultrasonic Phased Array (PA) module with signal processing and imaging technology for autonomous non-destructive evaluation of composite aerospace structures. We analyse two different sets of ultrasonic scan data, acquired from 5 MHz and 10 MHz PA transducers. Although higher frequency transducers promise higher axial (depth) resolution in PA imaging, we face several signal processing challenges to detect defects in compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Praveen et al [ 24 ] used higher order wavelets to enhance ultrasonic signal quality. In work by Mohammadkhani et al [ 25 ], the strongest echo which can be found from ultrasonic echo signal by wavelet transform, is combined with echo-fit search methodology to locate all effective echoes through multiple iterations. In work by Luo et al [ 26 ], a new wavelet thresholding function based on soft and hard thresholding functions was proposed to denoise the ultrasonic signal and the SNR reached 17.2634.…”
Section: Introductionmentioning
confidence: 99%
“…Praveen et al [ 24 ] used higher order wavelets to enhance ultrasonic signal quality. In work by Mohammadkhani et al [ 25 ], the strongest echo which can be found from ultrasonic echo signal by wavelet transform, is combined with echo-fit search methodology to locate all effective echoes through multiple iterations. In work by Luo et al [ 26 ], a new wavelet thresholding function based on soft and hard thresholding functions was proposed to denoise the ultrasonic signal and the SNR reached 17.2634.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ultrasonic phased arrays, guided wave detection technology, electromagnetic ultrasonic testing technology, and laser ultrasonic testing technology are proposed to improve the inspection capability. A phased ultrasonic array (PAUT) [ 41 , 42 ] can overcome the limitations of traditional UT. In PUAT, the transducer is composed of several independent piezoelectric chips.…”
Section: Non-destructive Testing (Ndt) For In-line Inspectionmentioning
confidence: 99%
“…Before generating the C-scan image, each A-scans requires signal amplification, known as time-gain compensation, time-domain alignment of the A-scans, followed by ToF extraction of the first maximum peak after the front surface echo. Hilbert transform was used to find the maximum echo after the dead-zone, and maximum echo is time-tracked for the damage-depth information based on a specified threshold in each A-scan [35]. Furthermore, time-domain alignment of all A-scans is initially essential to account for delays in the arrival of the ultrasonic reflection from the top surface of the specimen due to composite surface flatness variations.…”
Section: Pa Inspection Data Post-processingmentioning
confidence: 99%